(untitled) (Research, Society and Development, 2022)
Chronic kidney disease (CKD) is a condition caused by different factors that damage the kidney and impair its functions. In cases of more advanced stages, it becomes necessary to perform dialysis therapy for patients with CKD. year 2020, had approximately 133 thousand people on dialysis treatment. Given this complex situation, the question was: how can nursing care contribute to improving the quality of life of patients with CKD? The aim of the research was to identify the effects of the systematization of nursing care in optimizing the quality of life of patients with chronic renal dysfunction. This is an integrative review carried out with the descriptors in health sciences (DeCS): "Nursing Process" "Renal Failure" hemodialyse, dialyse and "Quality of life" that were organized in the search fields of the databases with Boolean operators (AND, OR and NOT). Searches were performed in the PubMed and Cochrane Library databases. Initially, 392 studies were found, and a total of 9 studies were included in the final synthesis of this research. The results of this research showed that nursing care can improve the quality of life of patients with chronic kidney disease in terms of reduction: of pain, blood pressure, depressive symptoms and improvement: of self-care, sleep quality, self-perception, mood and well-being. Nursing can still contribute with guidelines for changing the lifestyle of patients on dialysis therapies so that they can optimize the improvement of quality of life.